Stop the killing: how to end the mass shooting crisis - Schweit, Katherine W. (Rowman & Littlefield, 2022)
"Stop the Killing offers insight into what we can do to end the active shooter crisis plaguing America. The book is packed with training and sensible advice that takes readers through the latest research and best practices, making it a must read for every security-minded citizen and professional"--